18F‐FES PET/CT Influences the Staging and Management of Patients with Newly Diagnosed Estrogen Receptor‐Positive Breast Cancer: A Retrospective Comparative Study with 18F‐FDG PET/CT. (23rd July 2019) - Liu, Cheng; Gong, Chengcheng; Liu, Shuai; Zhang, Yingjian; Zhang, Yongping; Xu, Xiaoping; Yuan, Huiyu; Wang, Biyun; Yang, Zhongyi
Abstract: Purpose: We compared the clinical value of 16a‐18F‐fluoro‐17b‐estradiol ( 18 F‐FES) positron emission tomography (PET)/computed tomography (CT) and 18 F‐fluoro‐2‐deoxy‐D‐glucose ( 18 F‐FDG) PET/CT and investigated whether and how 18 F‐FES PET/CT affects the implemented management of newly diagnosed estrogen receptor positive breast cancer patients. Materials and Methods: We retrospectively analyzed 19 female patients newly diagnosed with immunohistochemistry‐confirmed estrogen receptor (ER)‐positive breast cancer who underwent 18 F‐FES and 18 F‐FDG PET/CT within 1 week in our center. The sensitivity of 18 F‐FES and 18 F‐FDG in diagnosed lesions were compared. To investigate the definite clinical impact of 18 F‐FES on managing patients with newly diagnosed ER positive breast cancer, we designed two kinds of questionnaires. Referring physicians completed the first questionnaire based on the 18 F‐FDG report to propose the treatment regime, and the second was completed immediately after reviewing the imaging report of 18 F‐FES to indicate intended management changes. Results: In total, 238 lesions were analyzed in 19 patients with newly diagnosed ER‐positive breast cancer. Lesion detection was achieved in 216 sites with 18 F‐FES PET and in 197 sites with 18 F‐FDG PET/CT. These results corresponded to sensitivities of 90.8% for 18 F‐FES versus 82.8% for 18 F‐FDG PET/CT in diagnosed lesions. Thirty‐five physicians were given the questionnaires referring to the treatment strategy, with 27 of them completing both questionnaires. The application of 18 F‐FES in addition to 18 F‐FDG PET/CT changed the management in 26.3% of the 19 patients with newly diagnosed ER‐positive breast cancer. Conclusion : Performing 18 F‐FES PET/CT in newly diagnosed ER‐positive breast cancer patients increases the value of diagnosis equivocal lesions and treatment management compared with 18 F‐FDG PET/CT. Implications for Practice: This study investigated whether 16a‐18F‐fluoro‐17b‐estradiol ( 18 F‐FES) positron emission tomography (PET)/computed tomography (CT) affects the clinical management of patients with newly diagnosed estrogen receptor (ER)‐positive breast cancer. Physicians completing two questionnaires comparing the clinical impact of 18F‐FES and 18F‐FDG on individual management plans in patients with newly diagnosed ER‐positive breast cancer confirmed that 18F‐FES scans led to change in management in 26.3% of the 19 patients with newly diagnosed ER positive breast cancer. This retrospective study indicates the potential impact of 18F‐FES PET/CT on intended management of patients with newly diagnosed estrogen receptor positive breast cancer in comparison to 18F‐fluoro‐2‐deoxy‐D‐glucose PET/CT. Abstract : This study evaluated and compared the clinical impact of 18F‐FES and 18F‐FDG on the sensitivity of lesion detection, correct staging and individual management plans in patients with newly diagnosed ER positive breast cancer.